LITERATUR REVIEW MISKONSEPSI FISIKA PESERTA DIDIK SMA DAN INSTRUMEN DIAGNOSISNYA - Santoso, Aprilia Nurhijriyah; Setyarsih, Woro (JPFT (Jurnal Pendidikan Fisika Tadulako Online), 2021)
This study aims to analyze the research trends of students' misconceptions of physics at the high school level and their diagnostic instruments. The research method used was literature study through bibliometric analysis. The research data were obtained from 25 articles selected through Publish or Perish on the Scopus database indicated from 2016 to 2020. The selected articles have the same type of diagnostic test instrument with several levels (Multiple-Tier) in high school students. The results of data analysis show that the publication of misconception articles of students at the high school level in the last five years has increased and increased, which means that misconceptions are still the focus of current research and the problem of misconceptions in physics is still common among high school students. The cause of the majority of students 'misconceptions in physics occurs due to internal factors in the form of incompatibility of students' preconceptions with the concept of scientists. The development of the Four-Tier test diagnostic instrument is a method to detect the misconceptions of physics that are often developed in research, because it is more effective and more accurate in identifying student misconceptions and the material that is often studied for misconceptions is mechanics. In addition, this study also reveals that Ida Kaniawati is the author who contributed the most to research misconceptions of physics and Taslidere's article (2016) is one of the most cited articles.